2020
DOI: 10.1038/s41392-020-00296-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune characteristics of severe and critical COVID-19 patients

Abstract: Dear Editor, Recently, the novel coronavirus disease (COVID-19) has broken out worldwide, 1 with rapid increase of infected patients. COVID-19 dominantly leads to pneumonia. 2 Among these COVID-19 patients, some appears to be severe symptoms with acute respiratory distress syndrome, organ failure, 2 and further present a poor outcome. Previous studies have been reported that immune patterns are closely associated with disease progression of patients infected with other viruses. 3 The correlation between immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…Lymphocytopenia is a prevalent COVID-19 marker, with reduced NK cell counts reported during infection ( Yang et al, 2020 ). The NK cell numbers were analyzed to determine whether any long-term decrease in NK cell numbers occurs as a result of SARS-CoV-2 infection and whether post-infection changes in NK cell numbers are associated with the severity of the clinical disease manifestation.…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocytopenia is a prevalent COVID-19 marker, with reduced NK cell counts reported during infection ( Yang et al, 2020 ). The NK cell numbers were analyzed to determine whether any long-term decrease in NK cell numbers occurs as a result of SARS-CoV-2 infection and whether post-infection changes in NK cell numbers are associated with the severity of the clinical disease manifestation.…”
Section: Resultsmentioning
confidence: 99%
“…Elimination of the virus mainly depended on the autoimmune system of patients. A recent study reported SARS-CoV-2 pneumonia patients with high lymphocyte levels, excluding B cells, and with low Interleukin-6 (IL-6) or Interleukin-10 (IL-10) levels, had a better survival rate (21). Early nutritional intervention could enhance the therapeutic effect of severe pneumonia patients with ARDS and reduce systemic inflammatory response (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphopenia in COVID-19 predominantly reflects T cell depletion, whereas B cell numbers are preserved. 127 Naive T cells tend to be diminished in the elderly, a finding associated with a poor prognosis. 128 Greater disease severity is also associated with lower levels of circulating spike-specific TfH cells and lower numbers of CD8+ IFNg+ T cells, whereas T17 cells were not generally detected.…”
Section: Indirect Myocardial Effectsmentioning
confidence: 99%